Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-28T17:51:03+01:00
A)Mg(OH)₂ + 2HCl ---> MgCl₂ + 2H₂O
b)3KOH + H₃PO₄ ---> K₃PO₄ + 3H₂O
C)Zn(OH)₂ + 2HNO₃ --> Zn(NO₃)₂ + 2H₂O
D)2Fe(OH)₃ + 3H₂SO₄ --> Fe₂(SO₄)₃ +6 H₂O
E)2NH₃ + H₂S --> (NH₄)₂S
ZAD2
Ba(OH)₂ + 2HNO₃ --->Ba(NO₃)₂ + 2H₂O
Ba²⁺ + 2OH⁻ + 2H⁺ + 2NO₃⁻ ----> Ba²⁺ + 2NO₃⁻ + 2H₂O
2OH⁻+2H⁺---->2H₂O
B)
2KOH + H₂SO₄----> K₂SO₄ + 2H₂O
2K⁺ + 2OH⁻+ 2H⁺ + SO₄²⁻ ---> 2K⁺ + SO₄²⁻ +2H₂O
2OH⁻+2H⁺---->2H₂O
C)Ca(OH)₂ + 2HMnO₄ --->Ca(MnO₄)₂ + 2H₂O
Ca²⁺+2OH⁻ +2H⁺ + 2MnO₄⁻ ---> Ca²⁺+ 2MnO₄⁻+ 2H₂O
2OH⁻+2H⁺---->2H₂O
D)
2LiOH + H₂CrO₄---->Li₂CrO₄ +2H₂O
2Li⁺+2OH⁻+2H⁺+CrO₄²⁻---->2Li⁺+CrO₄²⁻+2H₂O
2OH⁻+2H⁺---->2H₂O
ZADLAST
MeOH + HR ---> MeR + H₂O
Me⁺ + OH⁻ + H⁺+R⁻ ---> Me⁺ + R⁻+ H₂O
OH⁻ + H⁺-->H₂O
16 3 16
  • Użytkownik Zadane
2010-02-28T18:18:18+01:00

1
Rekacja zobojętniania polega na łaczeniu się wodorotlenków metali i kwasów w wyniku czego powstaje sół i woda
2
a)Mg(OH)2 + 2HCl > MgCl2 + 2H2O
b)3KOH + H3PO4> K3PO4 + 3H2O
c)Zn(OH)2 + 2HNO3> Zn(NO3)2 + 2H2O
d)2Fe(OH)3 + 3H2SO4> Fe2(SO4)3 +6 H2O
e)2NH3 + H2S > (NH4)2S
3
a)Ba(OH)2 + 2HNO3 >Ba(NO3)2 + 2H2O
Ba²⁺+2OH⁻+2H⁺+2NO3⁻> Ba²⁺ + 2NO3⁻ + 2H2O
2OH⁻+2H⁺>2H2O
b)2KOH + H2SO4> K2SO4 + 2H2O
2K⁺+2OH⁻+ 2H⁺+ SO4²⁻> 2K⁺ + SO4²⁻ +2H2O
2OH⁻+2H⁺>2H2O
c)Ca(OH)2 + 2HMnO4 >Ca(MnO4)2 + 2H2O
Ca²⁺+2OH⁻ +2H⁺ + 2MnO4⁻> Ca²⁺+ 2MnO4⁻+ 2H2O
2OH⁻+2H⁺>2H2O
d)2LiOH + H2CrO4>Li2CrO4 +2H2O
2Li⁺+2OH⁻+2H⁺+CrO4²⁻>2Li⁺+CrO4²⁻+2H₂O
2OH⁻+2H⁺>2H2O
4
MeOH + HR > MeR + H2O
Me⁺+OH⁻+H⁺+R⁻ > Me⁺+R⁻+ H2O
OH⁻+ H⁺>H2O
14 3 14